(untitled) (International Journal of Engineering and Computer Science, 2024)
Cyberbullying has been identified as a biggest problem for the last decade. In this paper we will discuss some recent findings and focus on general concepts within the area. This paper covers issues like repetition and power imbalance, types of cyberbullying, age, cyberbullying and traditional bullying, motives for and impact of cyber victimization, coping strategies, and prevention/intervention possibilities. Understanding the characteristics and methods of typical cybercrimes can help us better arm ourselves with the information and resources needed to reduce risks, improve cyber-security, and protect our online identities. However, hackers, phishing fraudsters, and other cybercriminals seized the chance to profit greatly from this chaos. Phishing assaults and cybercrime complaints have skyrocketed throughout the epidemic, putting a great deal of people & small organizations at danger of identity theft, credit card fraud, or data breaches.